Quantity and Size Distribution of Cough-Generated Aerosol Particles Produced by Influenza Patients During and After Illness - Lindsley, William G.; Pearce, Terri A.; Hudnall, Judith B.; Davis, Kristina A.; Davis, Stephen M.; Fisher, Melanie A.; Khakoo, Rashida; Palmer, Jan E.; Clark, Karen E.; Celik, Ismail; Coffey, Christopher C.; Blachere, Francoise M.; et al. (Journal of occupational and environmental hygiene, 2012)
The question of whether influenza is transmitted to a significant degree by aerosols remains controversial, in part, because little is known about the quantity and size of potentially infectious airborne particles produced by people with influenza. In this study, the size and amount of aerosol particles produced by nine subjects during coughing were measured while they had influenza and after they had recovered, using a laser aerosol particle spectrometer with a size range of 0.35 to 10 μm. Individuals with influenza produce a significantly greater volume of aerosol when ill compared with afterward (p = 0.0143). When the patients had influenza, their average cough aerosol volume was 38.3 picoliters (pL) of particles per cough (SD 43.7); after patients recovered, the average volume was 26.4 pL per cough (SD 45.6). The number of particles produced per cough was also higher when subjects had influenza (average 75,400 particles/cough, SD 97,300) compared with afterward (average 52,200, SD 98,600), although the difference did not reach statistical significance (p = 0.1042). The average number of particles expelled per cough varied widely from patient to patient, ranging from 900 to 302,200 particles/cough while subjects had influenza and 1100 to 308,600 particles/cough after recovery. When the subjects had influenza, an average of 63% of each subject's cough aerosol particle volume in the detection range was in the respirable size fraction (SD 22%), indicating that these particles could reach the alveolar region of the lungs if inhaled by another person. This enhancement in aerosol generation during illness may play an important role in influenza transmission and suggests that a better understanding of this phenomenon is needed to predict the production and dissemination of influenza-laden aerosols by people infected with this virus. [Supplementary materials are available for this article. Go to the publisher's online edition of Journal of Occupational and Environmental Hygiene for the following free supplemental resources: a PDF file of demographic information, influenza test results, and volume and peak flow rate during each cough and a PDF file containing number and size of aerosol particles produced.]